G70(P) Emergency endoscopy in accidental corrosive poisoning in children... to do or not to do?. (7th April 2014) - Saha, A; Bhaduri, M; Bhaduri, B
Abstract : Objectives and study aim: Exposure of ammonia by any route is rare but poisoning in children is almost always from the accidental ingestion of household cleaner. Ingestion can result in corrosive damage to the mouth, oesophagus and stomach. Management is largely supportive. We report a case of accidental ammonia poisoning in a child who underwent an emergency endoscopy, a first reported case of emergency endoscopy in a child at a District General Hospital (DGH) in the UK. The role of emergency endoscopy in such situations is reviewed. Methods: A two year old boy presented to the local district general hospital with drooling after having accidentally ingested a household cleaning solution, the main ingredient of which was ammonium hydroxide. Because of the history of ingestion of a corrosive alkali, an emergency endoscopy under general anaesthesia was undertaken by a consultant paediatric gastroenterologist, with an adult upper GI surgeon also on standby. Results: The endoscopy revealed areas of significant corrosion, ulceration and bleeding in the oesophagus and the stomach. There was no corrosive damage seen in the duodenum. The procedure was uneventful, and the child was commenced on treatment with intravenous analgesia, Omeprazole and oral Sucralfate. He made good clinical progress and within 48 h of admission, he was back to his normal self, eating and drinking normally, and was discharged home. A repeat endoscopy and an upper GI contrast study is planned after review in a few days time. Conclusion: In the past 30 years, paediatric endoscopy has evolved from an infrequent investigation in the operating room to a routine procedure, albeit usually performed almost exclusively in specialised centres rather than in DGHs, as in the case of our report. In recent times there has been debate on the usefulness of emergency endoscopy in such situations, especially in asymptomatic cases. An Italian multicentre study showed that the risk of severe damage increased proportionally with the number of signs and symptoms; alluding that routine emergency endoscopy in asymptomatic patients was not necessary. This article highlights the ill-defined role of emergency endoscopy in accidental corrosive poisoning in children and also opens a discussion whether the provision of emergency paediatric endoscopy services in the UK are optimally placed to cater to managing such cases.